Fantastic Four : Imaginauts - Waid, Mark (Marvel Worldwide, 2025)
Mark Waid and Mike Wieringo take the reins of FANTASTIC FOUR and deliver some of the most daring and humorous adventures Marvel's First Family has ever seen! Giant bugs! Living equations! Johnny Storm, CEO! Exploding unstable molecules! The secret behind the Yancy Street Gang! And watch as the antics between the Thing and the Human Torch heat up like never before! Prepare to laugh and cheer at once!